Hubungan Speed Dan Agility Terhadap Kemampuan Menggiring Bola Pada Atlet SSB Poleang Raya Kabupaten Bombana - Jumaking Jumaking; Muhammad Yusri Yusuf; Rahedin Suwo; Rosti Rosti; Iyan Nurdiyan Haris; La Ode Maklum Sabrin (Departement of Mathematics Education, 2024)
The purpose of this study was to determine the relationship between Speed ​​and Agility on the ability to dribble on the SSB Poleang Raya athlete, Bombana Regency. This research is a quantitative study using a descriptive correlational method. The research subjects were the SSB Poleang Raya athlete, Bombana Regency, which consisted of 30 people. The instruments used in this study were 40 meter run, shuttle run, and dribbling. Data analysis techniques were analyzed using statistical techniques using the SSPS.version 24 application. The results of this study indicate that there is a significant relationship of 0.038 and has a correlation coefficient that speed has a very strong positive relationship to the ability to dribble and has a contribution of 0.467*. There is a significant relationship of 0.036 and has a correlation coefficient value that agility has a very strong positive relationship to the ability to dribble and has a mem contribution value of 0.471* There is a significant relationship of 0.034 and has an interpretation of the correlation coefficient value that speed and agility have a significant relationship very strong positive effect on the ability to dribble and has a contribution of 0.574